1985
DOI: 10.1017/s0142716400006238
|View full text |Cite
|
Sign up to set email alerts
|

Writing in preschoolers: An age-related analysis

Abstract: We investigated the development in preschoolers' conceptualization of the written system from its graphic rendering and its mapping onto meaning by analyzing children's writings and readings of their writings. Forty-two Israeli children aged 3.4 -5.8 years were asked to draw, write, and interpret a number of utterances. By the age of four, children's writings became constricted in size relative to their drawings and were composed of linearly organized units separated by regular blanks. These units increased in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
44
2
4

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 14 publications
4
44
2
4
Order By: Relevance
“…The use of referential color was fairly common in this study, more common than writing a word for a large object with more marks or larger marks than writing a word for a small object. Tolchinsky-Landsmann and Levin (1985) made similar observations among Israeli 3-to 5-year-olds, and Ferreiro and Teberosky (1982) observed that Argentinean children sometimes produced longer lines of scribble when writing words that stood for large objects than when writing words that stood for small objects.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…The use of referential color was fairly common in this study, more common than writing a word for a large object with more marks or larger marks than writing a word for a small object. Tolchinsky-Landsmann and Levin (1985) made similar observations among Israeli 3-to 5-year-olds, and Ferreiro and Teberosky (1982) observed that Argentinean children sometimes produced longer lines of scribble when writing words that stood for large objects than when writing words that stood for small objects.…”
Section: Introductionmentioning
confidence: 63%
“…In such cultures, children produce conventional or near-conventional versions of their names at a time when they produce primitive renditions of other words. For example, the Israeli 4-and 5-year-olds studied by Tolchinsky-Landsmann and Levin (1985) were more likely to use real Hebrew letters when writing their names than when writing other targets and were more likely to use correct letters. Levin, Both-de Vries, Aram, and Bus (2005) also reported that Israeli and Dutch children were more advanced at writing their own names than at writing other words.…”
Section: Introductionmentioning
confidence: 99%
“…While researchers have differed in the number of discrete stages they identify, historically it appears that children follow a similar developmental pattern (see also, Hildreth, 1936;Luria, 1978;Ferreiro, 1978Ferreiro, , 1985. Iris Levin's numerous studies on Hebrew-speaking children's early literacy development include children from 3-6 years, generally before they begin to use conventional letters (e.g., Tolchinsky-Landsmann & Levin, 1985;1987). The belief that literacy should "be viewed as a system of representation of the deep lexicalmorphemic levels of language from the very beginning stages of acquisition" (Tolchinsky-Landsmann & Levin, 1987, p. 322) led this group of researchers to begin with 3-year-olds.…”
Section: Invented Spellingmentioning
confidence: 99%
“…Tolchinsky-Landsmann and Levin (1985Levin ( , 1987also Levin, Landsman & Tolchinsky, 1989) showed that almost half the children used referential strategies when writing or reading. That is, children justified their responses based on size, shape, or color characteristics of the object the words represented, rather than on the basis of the letters composing the word (see also Olson & Pelletier, 2002).…”
Section: Invented Spellingmentioning
confidence: 99%
“…The vast research on children's emergent writing shows constructive evolution which is based on the specific written system to which the children are exposed, including rich commonalities in this development between children exposed to different languages such as Hebrew, English, Spanish Italian and French (Tolchinsky-Landsmann and Levin 1985). This development moves from writing scribbles to symbolic writing (representing the word "sun" with a yellow color) to random letters and to conventional spelling.…”
mentioning
confidence: 99%